Bird and invertebrate communities appear unaffected by fracking traffic along rural roads despite dust emissions - Spiess, Jonathan (Ambio, 2019)
The development of shale petroleum resources has industrialized rural landscapes. We investigated how traffic from energy development expands and intensifies the road-effect zone through increased dust exposure, and how birds and invertebrates inhabiting the road-effect zone in agricultural areas of the Bakken region might be affected by dust exposure. We used dust collectors, trail cameras, and sweep-netting at increasing distances from unpaved roads to determine dust deposition, relative bird abundance, and invertebrate abundance, respectively. We found that traffic associated with fracking along unpaved roads emitted substantial dust 180 m into adjacent crop fields. But neither bird abundance or behavior, nor invertebrate abundance or community composition, appeared to be affected by dust or traffic. These findings suggest that wildlife in previously intensified agricultural landscapes like crop fields are resilient to intensification from energy development, but the same might not be true for wildlife in previously undisturbed habitat.